Unilateral Opening of Rat Blood-Brain Barrier Assisted by Diagnostic Ultrasound Targeted Microbubbles Destruction. (4th August 2016) - Xu, Yali; Cui, Hai; Zhu, Qiong; Hua, Xing; Xia, Hongmei; Tan, Kaibin; Gao, Yunhua; Zhao, Jing; Liu, Zheng
Abstract : Objective . Blood-brain barrier (BBB) is a key obstacle that prevents the medication from blood to the brain. Microbubble-enhanced cavitation by focused ultrasound can open the BBB and proves to be valuable in the brain drug delivery. The study aimed to explore the feasibility, efficacy, and safety of unilateral opening of BBB using diagnostic ultrasound targeted microbubbles destruction in rats. Methods . A transtemporal bone irradiation of diagnostic ultrasound and intravenous injection of lipid-coated microbubbles were performed at unilateral hemisphere. Pathological changes were monitored. Evans Blue extravasation grades, extraction from brain tissue, and fluorescence optical density were quantified. Lanthanum nitrate was traced by transmission electron microscopy. Results . After diagnostic ultrasound mediated microbubbles destruction, Evans Blue extravasation and fluorescence integrated optical density were significantly higher in the irradiated hemisphere than the contralateral side (all p < 0.01 ). Erythrocytes extravasations were demonstrated in the ultrasound-exposed hemisphere (4 ± 1, grade 2) while being invisible in the control side. Lanthanum nitrate tracers leaked through interendothelial cleft and spread to the nerve fiber existed in the irradiation side. Conclusions . Transtemporal bone irradiation under DUS mediated microbubble destruction provides us with a more accessible, safer, and higher selective BBB opening approach in rats, which is advantageous in brain targeted drugs delivery.